Microstructure investigations on nano-geopolymer cement cured under HPHT conditions - Ridha, S. (Asian Research Publishing Network, 2016)
Utilizing industrial by-products such as fly ash as raw materials for geopolymer cement has been highlighted as a better alternative to widely used comparing to Ordinary Portland Cement (OPC). Manufacturing process of OPC are proven emitting large amount of carbon dioxide (CO2), one of the main greenhouse effect. While, in terms of performance, OPC creates high permeability between cement particles when exposes to High Pressure High Temperature (HPHT) conditions inside the wellbore. Despite proven to have superior mechanical properties, basic geopolymer cement still encountered problems when applied in the same condition. This paper investigates the strength development of geopolymer cement admixed with nano-silica, SiO2 cured under temperature of 120Â°C and pressure of 4000 psi. It encompasses the microstructure change of the cement in terms of pore structures. The compressive strength development is tested using compressive strength tester, while the microstructural analysis are studied using Scanning Electorn Microscope (SEM) and X-Ray Diffraction (XRD). Results indicated that substantial increase in compressive strengthonce nano-silica is admixed. Pore distribution is improved due to nano-silica in geopolymer cement. This nanomaterial in geoploymer cement has better performance under HPHT condition than standard OPC and base geopolymer cement. Â© 2006-2016 Asian Research Publishing Network (ARPN).